Pengaruh Perbedaan Jenis Kedelai terhadap Kualitas Mutu Tahu - Nuri Andarwulan; Lilis Nuraida; Dede R. Adawiyah; Ria Noviar Triana; Denny Agustin; Desty Gitapratiwi (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2018)
Tofu is a processed product which is produced by coagulation process of soybean protein extract. The objectives of this study were to evaluate the relation of soybean variety to physicochemical characteristics during processing and the charactiristics of tofu. The soybean (IP new, IP 1 year old, US, Argentina, Indonesia) had moisture content (8.67-9.95%), ash content (5.15-5.36%), protein content (30.33-36.49%),  fat content (15.91-25.11%) and carbohydrate (26.98-35.00%). The highest yield of tofu was found in soybean IP New that was 195.60%, with tofu water content (80.18-83.17%), protein content (8.83-10.69%), and fat content (3.94-6.31%). The highest total solid was found in tofu from Argentina soybean that was 19.82%, while the density of tofu relatively similar (1%) to other tofu. The highest protein recovery and total solid recovery were found in tofu from Argentina soybean (62.05% and 39.62%). Argentina soybean was the best soybean which can be used to produce tofu. That soybean had the best protein recovery and based on texture quality analysis the soybean had similar characteristics with IP New soybean which had the best hardness, elasticity, and cohesiveness.